2018
DOI: 10.4168/aair.2018.10.6.675
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sublingual Immunotherapy in Elderly Rhinitis Patients Sensitized to House Dust Mites

Abstract: PurposeThis study aims to determine the efficacy and safety of house dust mite (HDM)-sublingual immunotherapy (SLIT) in elderly patients with AR.MethodsA total of 45 patients aged ≥ 60 years with HDM-induced AR who had ≥ 3 A/H ratio on skin prick test and/or ≥ 0.35 IU/L to both Dermatophagoides farinae and Dermatophagoides pteronyssinus by ImmunoCAP were enrolled in 4 university hospitals. To evaluate additional effects of HDM-SLIT, they were randomized to the SLIT-treated group (n = 30) or control group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, in a randomized not double‐blind trial, the administration of grass and birch SLIT was more effective than each individual allergen in patients with the dual sensitization, and a significant efficacy was seen for birch‐allergic subjects also in the grass season and vice‐versa . Finally, SLIT was demonstrated to be effective also in elderly patients, although this was not expected.…”
Section: The Recent History Of Slitmentioning
confidence: 98%
“…Interestingly, in a randomized not double‐blind trial, the administration of grass and birch SLIT was more effective than each individual allergen in patients with the dual sensitization, and a significant efficacy was seen for birch‐allergic subjects also in the grass season and vice‐versa . Finally, SLIT was demonstrated to be effective also in elderly patients, although this was not expected.…”
Section: The Recent History Of Slitmentioning
confidence: 98%
“…In studies addressing basophil activation, two favored lower expression of CD203c in BAT in AIT groups than placebo groups after 12-18 months of AIT. 36,47 Two studies found no intergroup difference after a relatively shorter duration of treatment (2-4 months). 48,49 One study demonstrated reduced expression of CD63 in the SCIT group after 6 months of treatment.…”
Section: Other Indicatorsmentioning
confidence: 97%
“…However, 2 studies, which suggest no significant changes in sIgG4 during AIT, were not included in the quantitative analyses because of insufficient data on sIgG4. 36,37 The result of the univariate meta-regression analysis was shown in Supplementary Table S2. In multivariate regression, route of AIT and time interval were covariates for sIgG4 (Table 3, R 2 ¼41.09%, I 2 ¼94.05%).…”
Section: Allergen-specific Igg4mentioning
confidence: 99%
See 1 more Smart Citation
“…The TNSS considers four common symptoms of AR: rhinorrhea, nasal obstruction, sneezing, and nasal itching. Each symptom is scored from 0 to 3 according to severity (11,17). The sum of the scores for all symptoms was calculated and that score was considered the primary endpoint.…”
Section: Primary and Secondary Endpointmentioning
confidence: 99%